2010
DOI: 10.1248/bpb.33.1199
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Arctiin and Arctigenin in Immunocompetent and Immunocompromised Mice Infected with Influenza A Virus

Abstract: Arctiin and its aglucone, arctigenin from the fruits of Arctium lappa L. showed potent in vitro antiviral activities against influenza A virus (A/NWS/33, H1N1) (IFV). Based on the data from time-of-addition experiments and on release tests of progeny viruses, arctigenin was assumed to interfere with early event(s) of viral replication after viral penetration into cells, and to suppress the release of progeny viruses from the host cells. Arctiin was orally effective against either IFV-inoculated normal or 5-flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
80
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 22 publications
0
80
0
1
Order By: Relevance
“…It has been reported to have multiple biological activities, such as anti-tumor, [1][2][3][4][5][6][7] anti-inflammatory, [8][9][10] and anti-viral [11][12][13][14][15] activities. Although ARG exhibits many pharmacological activities in vitro, ARG is too insoluble to be absorbed by the body, which limits its clinical applications.…”
mentioning
confidence: 99%
“…It has been reported to have multiple biological activities, such as anti-tumor, [1][2][3][4][5][6][7] anti-inflammatory, [8][9][10] and anti-viral [11][12][13][14][15] activities. Although ARG exhibits many pharmacological activities in vitro, ARG is too insoluble to be absorbed by the body, which limits its clinical applications.…”
mentioning
confidence: 99%
“…Arctigenin (purity >99%), isolated from dried seeds of A. lappa as previously described [17] , was provided by Dr Li-hong HU. Penicillin, streptomycin, Brefeldin A, compound C, 5-aminoimidazole-4-carboxamide ribonucleoside (AICAR), D-glucose, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and propidium iodide (PI) were purchased from Sigma (St Louis, Mo, USA).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…Roots of A. lappa have numerous therapeutic effects, and have been used in traditional medicine for treatment of arthritis, myelination, eczema, acne, and dysphasia (7). Pharmacological studies and clinical trials also indicated that burdock roots have antiinflammatory, free radical scavenging, antioxidant, anti-tumor, anti-viral, anti-bacterial, anti-fungal, cytotoxic and genotoxic activities (8)(9)(10)(11)(12)(13)(14)(15)(16). Due to the fewer side effects associated with herbal compounds compared to chemical agents, the effect of methanolic extract of A. lappa root was evaluated in this study.…”
Section: Introductionmentioning
confidence: 99%